2008
DOI: 10.1186/cc6988
|View full text |Cite
|
Sign up to set email alerts
|

Time course of plasma gelsolin concentrations during severe sepsis in critically ill surgical patients

Abstract: IntroductionGelsolin is an actin-binding plasma protein that is part of an 'actin-scavenging' system. Studies suggest that plasma gelsolin may play a crucial role in the pathophysiology of sepsis. Little is known about the course of plasma gelsolin levels over time in patients with severe sepsis. The aim of the study was to investigate plasma gelsolin levels in severe septic patients and to determine whether these levels predict the severity or clinical outcome of severe sepsis.MethodsNinety-one patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 28 publications
6
57
0
Order By: Relevance
“…In particular, pGSN is secreted into extracellular fluids. Serum pGSN levels decrease markedly in a variety of clinical conditions, such as lung injury [17], hepatitis B-associated liver cirrhosis [18], sepsis [19], major trauma [20], brain injury [21,22], certain cancers [23,24], Alzheimer's disease [25], rheumatoid arthritis [11] and multiple sclerosis [26]. Furthermore, certain studies have demonstrated that GSN is up-regulated in patients with idiopathic pulmonary fibrosis (IPF) or fibrotic nonspecific interstitial pneumonia [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pGSN is secreted into extracellular fluids. Serum pGSN levels decrease markedly in a variety of clinical conditions, such as lung injury [17], hepatitis B-associated liver cirrhosis [18], sepsis [19], major trauma [20], brain injury [21,22], certain cancers [23,24], Alzheimer's disease [25], rheumatoid arthritis [11] and multiple sclerosis [26]. Furthermore, certain studies have demonstrated that GSN is up-regulated in patients with idiopathic pulmonary fibrosis (IPF) or fibrotic nonspecific interstitial pneumonia [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Liver (parenchymal as well as nonparenchymal cells), lungs and spleen are responsible for the uptake of G-actin-DBP complexes by plasma membrane receptors [76]. Multiple studies have illustrated the important role of the actin scavenging system during severe sepsis [28,77], liver diseases [78,79], respiratory failure [80], preeclampsia [81,82], cardiac surgery [83] and after burn injuries [84].…”
Section: Vitamin D Binding Protein: What's In a Name?mentioning
confidence: 99%
“…That way, it protects essential organs from otherwise toxic F-actin, whose release goes up substantially during injury (6). Importantly, depleted levels of plasma gelsolin were found in many intensive care patients (7), and administration of exogenous gelsolin in mouse models of burn and sepsis showed a remarkable rate of recovery relative to placebo, promoting the concept of "gelsolin replacement therapy" (8). The existing understanding is that to stimulate its actin modulation functions, gelsolin primarily binds to Ca 2ϩ ions and gets activated, or in other words, undergoes shape changes that make it actin binding-competent (2,4).…”
mentioning
confidence: 99%